Transcranial direct current stimulation and power spectral parameters: a tDCS/EEG co-registration study - Mangia, Anna L.; Pirini, Marco; Cappello, Angelo (Frontiers in Human Neuroscience, 2014)
Transcranial direct current stimulation (tDCS) delivers low electric currents to the brain through the scalp. Constant electric currents induce shifts in neuronal membrane excitability, resulting in secondary changes in cortical activity. Concomitant electroencephalography (EEG) monitoring during tDCS can provide valuable information on the tDCS mechanisms of action. This study examined the effects of anodal tDCS on spontaneous cortical activity in a resting brain to disclose possible modulation of spontaneous oscillatory brain activity. EEG activity was measured in ten healthy subjects during and after a session of anodal stimulation of the postero-parietal cortex to detect the tDCS-induced alterations. Changes in the theta, alpha, beta and gamma power bands were investigated. Three main findings emerged: 1) an increase in theta band activity during the first minutes of stimulation; 2) an increase in alpha and beta power during and after stimulation; 3) a widespread activation in several brain regions.